Evaluation of tyre/road noise and texture interaction on rubberised and conventional pavements using CPX and profiling measurements. (14th September 2020) - de León, Gonzalo; Del Pizzo, Alessandro; Teti, Luca; Moro, Antonino; Bianco, Francesco; Fredianelli, Luca; Licitra, Gaetano
Abstract : Road traffic noise is the most common source of environmental pollution in urban areas, and therefore, the study of noise mitigation actions is fundamental for urban planning. The use of low noise road surfaces is one of the most widespread intervention since it acts directly on the source of road traffic noise, represented by tyre/road interaction. In this work, the interaction between texture and tyre/road noise was studied from an experimental point of view, by comparing CPX and road texture measurements on rubberised and standard road surfaces. Tyre deformation was addressed by taking into account the indenter method proposed by Sandberg and Goubert in 2018. Regressions of CPX and enveloped road texture levels were performed separating rubberised from reference surfaces, and parallelism tests were performed on the slopes. Results show that the use of rubber influences the interaction of road texture and noise, especially at high frequencies.